A comprehensive and efficient quality assurance program for an image-guided small animal irradiation system - Severin Kampfer; Manuela A. Duda; Sophie Dobiasch; Stephanie E. Combs; Jan J. Wilkens (Zeitschrift für Medizinische Physik, 2022)
In the field of preclinical radiotherapy, many new developments were driven by technical innovations. To make research of different groups comparable in that context and reliable, high quality has to be maintained. Therefore, standardized protocols and programs should be used. Here we present a guideline for a comprehensive and efficient quality assurance program for an image-guided small animal irradiation system, which is meant to test all the involved subsystems (imaging, treatment planning, and the irradiation system in terms of geometric accuracy and dosimetric aspects) as well as the complete procedure (end-to-end test) in a time efficient way. The suggestions are developed on a Small Animal Radiation Research Platform (SARRP) from Xstrahl (Xstrahl Ltd., Camberley, UK) and are presented together with proposed frequencies (from monthly to yearly) and experiences on the duration of each test. All output and energy related measurements showed stable results within small variation. Also, the motorized parts (couch, gantry) and other geometrical alignments were very stable. For the checks of the imaging system, the results are highly dependent on the chosen protocol and differ according to the settings. We received nevertheless stable and comparably good results for our mainly used protocol. All investigated aspects of treatment planning were exactly fulfilled and also the end-to-end test showed satisfying values. The mean overall time we needed for our checks to have a well monitored machine is less than two hours per month.